2010
DOI: 10.1165/rcmb.2009-0292oc
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Human Complement–Mediated Killing of Klebsiella pneumoniae

Abstract: With an in vitro system that used a luminescent strain of Klebsiella pneumoniae to assess bacterial metabolic activity in near-real-time, we investigated the dynamics of complement-mediated attack in healthy individuals and in patients presenting to the emergency department with community-acquired severe sepsis. A novel mathematical/statistical model was developed to simplify light output trajectories over time into two fitted parameters, the rate of complement activation and the delay from activation to the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…(10, 29) Bound C3b was quantified flow-cytometrically using a FITC-labeled anti-C3b antibody (Thermo-Scientific, Fremont, CA). Cells opsonized with heat-inactivated serum served as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…(10, 29) Bound C3b was quantified flow-cytometrically using a FITC-labeled anti-C3b antibody (Thermo-Scientific, Fremont, CA). Cells opsonized with heat-inactivated serum served as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that some strains of K. pneumoniae, which possesses certain serotypes of LPS (such as K1, K10 and K16), exhibited resistance mechanisms against the recognition and effector functions of the complement system (Merino et al, 1992;Alberti et al, 1996). However, when analyzing the proliferation of the bacteria in the scenario of absence of Factor B, the lack of activation of the classical pathway of the complement system seemed to support the bacterial proliferation almost exponentially, this result as also observed in a C5 depletion setup (Nypaver et al, 2010). Additionally, the intraperitoneal adoptive transference of the sera of mice immunized with extracellular vesicles of K. pneumoniae, led to protection from the lethality induced by the intraperitoneal challenge of a high dose of K. pneumoniae (Lee et al, 2015).…”
Section: Resultsmentioning
confidence: 70%
“…The activation of complement by direct cleavage of C3 by bacterial surface structures, such as LPS and outer membrane proteins, initiates the complement cascade by the alternative pathway. This activation of the complement system alternative pathway is prevalent in early stages of infection, while the activation of the classical and lectin pathway is present for prolonged infections (Nypaver et al, 2010). Previous studies have shown that some strains of K. pneumoniae, which possesses certain serotypes of LPS (such as K1, K10 and K16), exhibited resistance mechanisms against the recognition and effector functions of the complement system (Merino et al, 1992;Alberti et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CPS of K. pneumoniae resists the nonspecific host defense mechanism such as the complement cascade, which plays a crucial role in the early host defense against invading pathogens [59]. In vitro studies have shown that CPS inhibits the deposit of the C3 complement component onto the bacteria's surface and reduces the formation of the membrane attack corr'lplex [60,61].…”
Section: Complement Cascade Defensementioning
confidence: 99%